DAMPAK CKPN TERHADAP KINERJA OPERASIONAL: RISIKO DAN PROFITABILITAS BANK PERKREDITAN RAKYAT - Rahmawati, Anisa; Maulana, Ridho; Firmansyah, Amrie (Universitas Multimedia Nusantara, 2024)
Abstract - The financial performance of banking institutions reflects the efficiency and effectiveness of their operations, influenced by various internal and external factors. This study examines the effect of Loan Loss Provision (LLP) on the operating performance of Bank Perkreditan Rakyat (BPR). Using a quantitative approach, the research analyzes financial reports of BPRs supervised by the Otoritas Jasa Keuangan (OJK) from 2018 to 2022. Data were collected from the official websites of respective BPRs through online searches. A purposive sampling method was applied, resulting in a sample of 12 BPRs observed over 5 years. Hypothesis testing was conducted using multiple regression analysis with panel data. The results indicate that Loan Loss Provision (LLP) has a negative effect on operating performance, as measured by Return on Assets (ROA). This finding suggests that higher LLP allocations reduce profitability by limiting the capacity of BPRs to extend credit and generate interest income. The study contributes to understanding how risk management practices, particularly LLP, influence the financial outcomes of BPRs. It also provides insights for regulatory authorities, especially the Otoritas Jasa Keuangan (OJK), to evaluate the impact of LLP policies on BPR performance and their implications for the sustainability of small-scale banking operations. Keywords: Profitability; Loan Loss Provision; Operating Performance; Bank Perkreditan Rakyat